The Configurations of Informal Institutions to Promote Men’s and Women’s Entrepreneurial Activities - Junaid, Danish; Yadav, Amit; Afzal, Farman; Shah, Imran Ahmed; Shanmugam, Bharanidharan; Jonkman, Mirjam; Azam, Sami; De Boer, Friso (Frontiers in Psychology, 2020)
While previous studies have examined the impact of informal institutions to determine entrepreneurial activities, this paper explores the different configurational paths of informal institutions to promote men’s and women’s entrepreneurial activities across factor-driven and efficiency-driven economies. We collected data from the Global Entrepreneurship Monitor for 56 countries for the years 2008-2013 and employed fuzzy-set qualitative comparative analysis to conduct the empirical analysis. The results confirm that a single antecedent condition is unable to produce an outcome while combination of different conditions can produce an outcome. We find that cultural-cognitive institutional antecedents in combination with social-normative antecedents create configurations of conditions that lead to the higher levels of men’s and women’s entrepreneurial activities in factor-driven and efficiency-driven economies. Moreover, this study shows that these causal conditions configure differently to promote men’s and women’s entrepreneurial activities in factor-driven and efficiency-driven nations. This paper may create awareness in potential entrepreneurs regarding specific sets of institutional antecedents that can increase the emergence of entrepreneurship in different economic clusters. We show that institutional antecedents which are essential to promote entrepreneurship combine distinctly for men’s and women’s entrepreneurship and this combination varies in different stages of economic development.